Scalable geographic routing algorithms for wireless ad hoc networks. - Frey, H. (IEEE Network : the magazine of global information exchange)
The design of efficient routing protocols for dynamical changing network topologies is a crucial part of building power-efficient and scalable ad hoc wireless networks. If position information is available due to GPS or some kind of relative positioning technique, a promising approach is given by geographic routing algorithms, where each forwarding decision is based on the positions of current, destination, and possible candidate nodes in vicinity only. About 15 years ago heuristic greedy algorithms were proposed, which in order to provide freedom from loops might fail even if there is a path from source to destination. In recent years planar graph traversal has been investigated as one possible strategy to recover from such greedy routing failures. This article provides a tutorial for this class of geographic routing algorithms, and discusses recent improvements to both greedy forwarding and routing in planar graphs.